Performance evaluation of underlay cognitive hybrid satellite–terrestrial relay networks with relay selection scheme. Issue 16 (1st October 2019) - Lai, Ping; Bai, Hang; Huang, Yunlai; Chen, Zhuang; Liu, Tianjian
Abstract : The applicability of cognitive radio (CR) techniques into satellite communications has received considerable attention in recent years. This study considers the integration of relay transmission into CR‐based satellite terrestrial network, which offers the advantages of not only increasing the overall spectral efficiency by spectrum sharing but also extending the wireless coverage through the deployment of relays. Specifically, the authors derive the exact closed‐form expression of the outage probability (OP) for the cognitive network, which provide an efficient means to evaluate the impact of key parameters on the system performance. Furthermore, the asymptotic OP expression at high signal‐to‐noise ratio is presented, which reveals the achievable diversity order and coding gain of the considered network. Finally, numerical results are carried out to validate the theoretical results, and shows that although a higher transmit power or weaker shadowing severity of the satellite interference link has a severe detrimental impact on the outage performance of the cognitive network by reducing the coding gain, the achievable diversity order only depends on the fading severities and the number of relays of the cognitive network.